Two new Opilio Herbst, 1798 species (Arachnida: Opiliones: Phalangiidae) from Azerbaijan - Snegovaya, N.y.; Bovykina, G.v.; Kondakov, A.v. (Zootaxa, 2025)
Two new opilionid species of the family Phalangiidae, Opilio ordubadicus Snegovaya sp. nov. and Opilio ilhamakerimovae Snegovaya sp. nov. are diagnosed, illustrated and described on the basis of morphological and molecular methods from the territory of Azerbaijan Republic. The first COI sequences for the following species—Opilio ordubadicus sp. nov., O. ilhamakerimovae sp. nov., O. apsheronicus Snegovaya, 2005, O. sylvestris Snegovaya, 2010 are provided for the first time.